Does placental abruption cause neonatal anemia?. (18th May 2022) - Bruinsma, Marieke A. W.; de Boer, Marjon A.; Prins, Sandra; Abheiden, Carolien N. H.
Abstract: Introduction: Placental abruption can result in serious perinatal morbidity and mortality. However, it is not clear whether placental abruption could lead to neonatal anemia, as a direct relation has not been described yet. The objective of this study is to investigate whether there is a relation between occurrence of placental abruption and neonatal anemia. Material and Methods: All women with a clinical diagnoses of placental abruption between January 2016 and April 2021 in Amsterdam UMC, from both the VU University Medical Center and Amsterdam Medical Center, were included. Demographic data and delivery outcomes were collected retrospectively using the medical files. The primary outcome was neonatal anemia, defined as hemoglobin levels less than the fifth percentile for gestational age. Results: A total of 65 mothers and 65 neonates were included in our study. Average gestational age was 30 + 5 weeks. Mean hemoglobin level of the neonates at birth was 16.5 g/dl (10.2 mmol/L) with hemoglobin levels comparable to the reference curve. Two neonates (3.6%) were diagnosed with anemia based on their hemoglobin level at birth, and six (9.2%) neonates received a blood transfusion within 24 h after birth. Conclusions: With this study, we found that the hemoglobin levels of the neonates born after placental abruption are comparable to the reference curve and do not show more neonates than expected below the fifth percentile for gestational age. It remains unclear whether there is fetal blood loss during a placental abruption but our results suggest that at least a big amount of fetal blood is not lost, since we did not found a large number of anemic neonates. Severe neonatal anemia in the case of placental abruption does not need to be expected.